2013
DOI: 10.4103/2229-5151.124164
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal perforation following cervical spine surgery: A review with considerations in airway management

Abstract: Anterior cervical discectomy and fusion (ACDF) is a commonly performed surgery for the treatment of spondylosis, radiculopathy, myelopathy, and trauma to the cervical spine. Esophageal perforation is a rare yet serious complication following ACDF with an incidence of 0.02 to 1.52%. We describe a case of a 24-year-old man who underwent ACDF and corpectomy following a motor vehicle accident who subsequently developed delayed onset esophageal perforation requiring surgical intervention. We believe that the detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Dysphagia is an underrecognized but significant complication of cervical fusion surgeries 1. The incidence of esophageal perforation after anterior cervical spine surgery is estimated to be between 0.02% and 1.49% with a mortality rate of 6% 2. Most esophageal erosions occur in the intraoperative or immediate postoperative setting, although there has been an increase in cases with delayed presentation, which often lead to dramatic clinical deterioration with a higher mortality risk of 20–50% 3.…”
Section: Case Reportmentioning
confidence: 99%
“…Dysphagia is an underrecognized but significant complication of cervical fusion surgeries 1. The incidence of esophageal perforation after anterior cervical spine surgery is estimated to be between 0.02% and 1.49% with a mortality rate of 6% 2. Most esophageal erosions occur in the intraoperative or immediate postoperative setting, although there has been an increase in cases with delayed presentation, which often lead to dramatic clinical deterioration with a higher mortality risk of 20–50% 3.…”
Section: Case Reportmentioning
confidence: 99%
“…1 According to reports, the incidence of esophageal perforation is low, ranging from 0.04 to 0.25%, [2][3][4] but it has a mortality rate as high as 20%. 5,6 Surgical repair of esophageal perforation is extremely challenging due to several reasons. The first is the difficulty in locating the fistula; the second is the movement of the esophagus during the suturing process, which is not conducive to suturing; and the third is severe edema of the esophageal muscular layer and erosion by gastric acid, which requires finding healthy tissue for suturing.…”
Section: Introductionmentioning
confidence: 99%
“…Primary repair also carries a high risk of secondary complications such as esophageal leakage and stricture, leading to reduced quality of life and high mortality rates. 7 Gerald et al 8 reported a 54% incidence of esophageal strictures after esophageal perforation repair, requiring multiple (3)(4)(5)(6)(7)(8)(9) postoperative endoscopic surgical dilations. Tanaka 9 reported that anastomotic stricture occurs in 13.6% of patients with esophageal repair after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A 5-year survey-based report of the Cervical Spine Research Society membership found an estimated prevalence of esophageal injuries during anterior cervical surgery to be 0.25%; 7 other reports in the literature describe frequencies ranging from 0% 8 to 1.62%, 9 thus corroborating the low overall prevalence of this pathology. 10 - 32 Prompt recognition of these injuries is critical, as perforations can lead to the formation of fistulae, abscesses, osteomyelitis, mediastinitis, sepsis, and death. Sealy described esophageal perforation as “the most rapidly fatal and serious perforation of the gastrointestinal tract.” 33 Patients with esophageal perforations will often present with vague complaints, making the condition difficult to diagnose and potentially delaying the onset of treatment.…”
Section: Introductionmentioning
confidence: 99%